1994
DOI: 10.1152/ajpendo.1994.267.6.e1002
|View full text |Cite
|
Sign up to set email alerts
|

A new method for the estimation of the components of energy expenditure in patients with major trauma

Abstract: The management of critically ill patients would be better understood if the total energy expenditure (TEE) and its components are known. To quantify the different components of energy expenditure in patients with major trauma, we used a technique combining measurements of body composition and oxygen consumption. We determined changes in body weight, total body water, total body protein, total body potassium, total body fat, and bone mineral content every 5 days over a 10-day period in a group of nine multiply … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…The present results, based on a number of published studies carried out in our facility (Franch-Arcas et al 1994;Monk et al 1996;Plank et al 1998) in which integrated ∆TBF have been measured over the first or second week after the onset of critical illness, confirm that fat is not an obligatory energy source in critically-ill patients. An earlier study of patients with sepsis from our laboratory (Streat et al 1987) suggested, on the basis of a less direct measurement of TBF, that aggressive nutritional support could prevent lipolysis.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The present results, based on a number of published studies carried out in our facility (Franch-Arcas et al 1994;Monk et al 1996;Plank et al 1998) in which integrated ∆TBF have been measured over the first or second week after the onset of critical illness, confirm that fat is not an obligatory energy source in critically-ill patients. An earlier study of patients with sepsis from our laboratory (Streat et al 1987) suggested, on the basis of a less direct measurement of TBF, that aggressive nutritional support could prevent lipolysis.…”
Section: Resultssupporting
confidence: 80%
“…TBF and bone mineral content were measured by dualenergy X-ray absorptiometry, TBP by in vivo neutron activation analysis and total body water by 3 H 2 O dilution. Total body mineral was obtained as the sum of bone mineral content and an estimated non-bone mineral content, while TBG was derived according to the following equation (Franch-Arcas et al 1994):…”
Section: Methodsmentioning
confidence: 99%
“…A total of 1653 articles were excluded for various reasons, leaving 15 articles for examination. Four studies using single‐frequency bioimpedance analysis and 5 studies with duplicate data were excluded, leaving 6 studies meeting the inclusion criteria . There were no discrepancies between researchers in terms of eligibility of the studies, data extraction, or study quality.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the nutrition provision in each study against these guidelines, energy and protein delivery were represented as mean kcal and grams of protein delivered/kg per day during the study period. Weight was taken as either the estimated mean participant weight reported in the study (actual or obesity‐adjusted body weight) or the measured weight on day 10, which has been reported to be the closest to pre‐illness weight …”
Section: Methodsmentioning
confidence: 99%
“…ECW/ICW reflects body hydration and FFM, and BCM reflects metabolic status (11, 12). Several studies have demonstrated that critically ill patients have considerable variation in energy expenditure patterns (1315). Within the ICU setting, hypermetabolism induced by disease and medical intervention results in accelerated loss of protein and fat.…”
Section: Discussionmentioning
confidence: 99%